The Concept of Healing Waterscapes in Public Open Spaces to Construct the Positive Psychology of Visitors - Prasandya, Km Deddy Endra; Satria, Made Wina; Adiartha, Made Arya (Talenta Publisher, 2024)
Public open spaces contain various features that have psychological effects on human mental health. Water, as one of the key elements in landscape design, not only enhances aesthetics but also provides sensory stimulation, social interaction, and psychological benefits. It possesses therapeutic qualities that promote relaxation and reduce stress. Given the rising prevalence of mental health issues among adolescents in Bali, public open spaces incorporating waterscapes play a crucial role. The concept of a